Peningkatan Peran Perguruan Tinggi Agama melalui Penataan Visi, Misi dan Sistem Pendidikan - Zurqoni, Zurqoni (IAIN Samarinda, 2011)
High-Islamic religious education has a role to prepare graduates who have the role of academic and professional capabilities and the ability of community. The role of universities is packaged in a tri-dharma which includes providing education and teaching, research and community service. The existence of religious colleges should be able to respond to currents of modernity and globalization that drive the transformation of civilization, the information revolution and the changes caused. Increasing the role of religion in the context of higher education begins by clarifying the paradigm of modernity, vision and mission to be able to accommodate and respond to various challenges of the times and demanding needs of the wider community. In this case the required increase in the quality of the education system to reinforce the existence of religious colleges, which includes academic personnel in accordance with the qualifications, students are selected based on qualifications, a curriculum that can respond to community needs, measurable educational goals, learning strategies to optimize the diverse abilities of students, academic facilities adequately, and stakeholders.